2016
DOI: 10.1515/bot-2015-0068
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the marine algae of the Bermudas. 15. Dichotomaria huismanii (Galaxauraceae, Rhodophyta), a new species in the D. marginata complex from the western Atlantic

Abstract: Notes on the marine algae of the Bermudas. 15. Dichotomaria huismanii (Galaxauraceae, Rhodophyta), a new species in the D. marginata complex from the western Atlantic DOI 10.1515/bot-2015-0068 Received 19 August, 2015 accepted 7 January, 2016; online first 4 February, 2016 Abstract: Using plastid-encoded rbcL and mitochondrial COI-5P sequence data, the species in Bermuda formerly recognized as Dichotomaria marginata was found to be a cryptic species in a wide complex of species all falling under the morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Red algal species are morphologically differentiated by the gross morphology of the thallus, including overall in situ appearance, thallus size, and branch length, as well as the characteristics of the sporophyte cortex, such as the size and shape of the different layers of cells composing the cortex. Previous studies comparing the morphology of Dichotomaria species have also relied on these traits (Tanaka, 1935;Kurihara et al, 2005;Wang et al, 2005;Liu et al, 2013;Wiriyadamrikul et al, 2014;Schneider et al, 2016). Building upon these diagnostic traits used for red algae, we have expanded the existing original account of D. elegans and D. latifolia (Tanaka, 1935) by providing newly generated morphological descriptions, micromorphology plates, and corresponding molecular data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Red algal species are morphologically differentiated by the gross morphology of the thallus, including overall in situ appearance, thallus size, and branch length, as well as the characteristics of the sporophyte cortex, such as the size and shape of the different layers of cells composing the cortex. Previous studies comparing the morphology of Dichotomaria species have also relied on these traits (Tanaka, 1935;Kurihara et al, 2005;Wang et al, 2005;Liu et al, 2013;Wiriyadamrikul et al, 2014;Schneider et al, 2016). Building upon these diagnostic traits used for red algae, we have expanded the existing original account of D. elegans and D. latifolia (Tanaka, 1935) by providing newly generated morphological descriptions, micromorphology plates, and corresponding molecular data.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological examinations of thalli of both tetrasporophytic and gametophytic plants were carried out for the three species within the D. marginata complex found in Taiwan: D. "marginata", "D. latifolia", and "D. elegans". We selected the following traits: gross morphology, color, habitat preference, external branch width, as well as specific characteristics of the gametophyte (epidermal cells and spine cells width and height) and tetrasporophyte (stalk cells height, outer cortical cells width and height, and the presence of apiculate tips), based on their established taxonomic relevance in previous Dichotomaria studies (Tanaka, 1935;Kurihara et al, 2005;Wang et al, 2005;Liu et al, 2013;Wiriyadamrikul et al, 2014;Schneider et al, 2016). The majority of stalk cells of the tetrasporophyte were dichotomous, attached to two outer cortical cells; therefore, to avoid bias, we only measured their height.…”
Section: Morphological Examinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its impregnation with calcium carbonate, the tips of specimens recently collected are nearly always truncated with a regrowth of medullary filaments emerging, clear evidence of prior herbivore grazing (Schneider et al 2016, figures 8, 9). Today's plants are half the size of mature 19th century plants (Schneider et al 2016, figure 7), sparsely branched, and rarely found, and only then as isolated individuals.…”
Section: Intertidal and Shallow Subtidal Speciesmentioning
confidence: 99%